Interdisciplinary Guidelines for Care of Women Presenting to the Emergency Department With Pregnancy Loss. Issue 1 (January 2018) - Catlin, Anita
Abstract : Abstract: In April 2016, the National Perinatal Association and Kaiser Permanente Northern California Nursing Research Community Benefits Grant sponsored an interdisciplinary summit to explore the needs of women who present with actual or potential pregnancy loss to the emergency department (ED). Thirty-two experts in the field of pregnancy loss, 17 of whom represented their professional organizations, participated. These experts, which included nurses, physicians, social workers, counselors, authors, and parents, worked together to create guidelines for care of women with a pregnancy loss in the ED. Recommendations for ED healthcare providers are included. Emergency department personnel agreed that improvements in care could be offered and were willing to endorse education for their staff. The guidelines delineate how to better provide physical, emotional, and bereavement support at any stage of gestational loss. Administrative support for policies in the ED is essential to ensure the delivery of family-centered, culturally sensitive practices when a pregnancy ends. Abstract : An interdisciplinary summit was held to explore the needs of women who present to the emergency department with actual or potential pregnancy loss. Thirty-two experts in the field of pregnancy loss, 17 of whom represented their professional organizations, participated. The guidelines that were developed delineate how to better provide physical, emotional, and bereavement support to woman and their families at any stage of pregnancy loss. Reprinted with permission from The National Perinatal Association.